Korea National Insurance Corporation v. Allianz Global Corporate & Specialty AG (on its own behalf and on behalf of the Reinsurers Subscribing to Policy Number AJFM157 for the 2004 Year of Account). (2016) - Unknown
Abstract : 605 Jurisdiction — Enforcement of foreign judgments — Defences to enforcement — Allegations of fraud — Alleged partiality of foreign judiciary — Justiciability — Judicial restraint — Adjudication of allegations of fraud against a State or leader — Embarrassment to diplomatic relations — Distinction between sovereign acts and commercial acts — Refusal to enforce foreign judgment on public policy grounds — Significance of absence of judicial or manageable standards by which to judge a sovereign act — The law of England